Nation, culture and family : identity in a Scottish/Australian popular song tradition - Dougal, Josephine Kathleen (Curtin University, 2010)
This study arose out of an interest in my own family’s Scottish song traditions and a desire to understand them within a wider cultural context. Its purpose is to create a critical account of music and migrant identity that brings insights from folklore studies, cultural studies, and migration and diaspora studies together to shed light on transcultural identity formation and maintenance. More specifically, it seeks to ‘discover’ an explanation for why and how the cultural resources/traditions that migrants bring with them continue to have force in migrant family life. It examines the complex of ways in which homeland and hereland are implicated in migrant identities, the role of cultural tradition and family in the migrant experience, and their part in shaping migrant memories, identities and concepts of ‘home’.In examining the salience of homeland culture in migrant family life, this study addresses one of the core questions in migration theory and research, that is, why and how migrants maintain connections to their homeland.1 Much of the migration theory and research that addresses this question focuses on the role of migrant communities and institutions, ethnic networks, and transnational social, economic and political ties, often stressing the connections between kinship groups and families across borders. Some of this work, in the fields of transnational migration and diaspora studies, has placed greater emphasis on the role of ‘imagined’ connections, and on the ways in which migrants make symbolic connections to a sense of homeland as a means of supporting new identities.2 It is these symbolic connections with homeland, rather than the social, political and economic that this study seeks to investigate. This investigation will focus on music as a source of symbolic connections to homeland, and its role in the construction of family and migrant identity.The study posits that national/cultural identity is not determined by membership, nor pervasive cultural constructions of identity, but is rather a process in which people draw upon, appropriate and customise these discourses in an active process of self-making. Its guiding proposition is that national/cultural identity arises in the intersection between the ‘nation’ and the individual, between the ‘public’ and ‘private’, and is mediated by the particular social and cultural contexts in which people operate - migration being one such context.The ways in which the ‘nation’ comes to have personal relevance at the local level is explored through the interchanges between public song traditions and localised forms of song tradition. The focus of the thesis is on the role of Scottish song culture in constructing representations of national/cultural identity, and how such cultural constructions, their modes of production and dissemination interact with local practices and meanings, and how these dynamics play out in the construction of migrant cultural identity.In pointing to how the ‘nation’ is made local in the context of migration, the study challenges the idea that cultural traditions are backward looking and regressive, and frozen in time in diaspora, arguing instead that tradition and the past are actively deployed as key cultural strategies in migrants’ creation of home and belonging. In doing so, it makes a case for how collective ideas of nation are appropriated and customised at the local level, and how the cultural construction of Scottishness in song, deployed in a Scottish/Australian migrant family, acted as important referents to their identity and gave shape and meaning to their formulations of Scottish/Australian identity.